Determining Factors of Human Development Index and Quality of Life by Regency/City in East Java Province in 2023 Using Factor Analysis Method - Qolbi, Nur Latifatul; Indriyana, Maharani; Wulandari, Sri Pingit (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The Human Development Index (HDI) is an important tool to measure the success of the development of quality of life and the development ranking of a country. East Java, the second most populous province in Indonesia, has a strategic role in this regard. Although the HDI of East Java continues to increase, there are still gaps between regions, for example the difference in HDI between Malang City and Sumenep Regency. This study uses the Principal Component Analysis method and factor analysis to reduce the various variables that affect the HDI and quality of life in East Java. Based on data from 38 regencies/cities on eight variables, two main factors were obtained, namely education and economy and employment, which have significant correlations, multivariate normal distributions, and meet the statistical requirements for factor analysis.